Assessment of the adverse effects of the acaricide amitraz: in vitro evaluation of genotoxicity - Padula, Gisel (2012)
Amitraz is a formamidine widely used in Veterinary Medicine for the treatment of ectoparasites. It is a highly liposoluble compound that is quickly absorbed through the skin and mucous membranes, thus making exposure potentially dangerous for humans and animals. The aim of this study was to compare the genotoxic potential of the active constituent of the insecticide amitraz and a commercial product containing amitraz in vitro in For Peer Review Only hamster cells. The induction of primary DNA damage was evaluated by alkaline single-cell gel electrophoresis (comet assay) and the apoptotic ability was examined by the Annexin V/PI staining assay. The commercial formulation significantly increased the index of DNA damage at concentrations of 2.50-3.75 µg/ml compared to the control. The active constituent only induced significant DNA damage with the highest concentration (3.75 µg/ml). Although both tested products increased the frequency of cell death, neither of them induced significant differences. Genotoxic potential is a primary risk factor for long-term effects such as carcinogenic and reproductive toxicology. Results presented here highlight the need for further investigation of the potential health risk of this veterinary medicine.